Audit Energi Sebagai Upaya Proses Efisiensi Pemakaian Energi Listrik Di Kampus Universitas Teuku Umar (UTU) Meulaboh - Muhammad Ikhsan; Maidi Saputra (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2018)
Electrical energy is one form of energy currently needed humans in everyday life. Projected load the higher the electrical energy requires the government to run the 10 thousand MW. Energy demand in Indonesia on average per year rose by 7%, while primary energy supply is only expected to increase by 2%. Thus, the development of energy sources other than oil and other fossil energy. Conserving energy is one important way to tackle the problem of energy, because the results can be felt in a relatively short time. Energy audit can help provide a picture of energy use, energy distribution, energy costs and energy conversion that eventually could be used to identify sources of energy waste. Teuku Umar University campus (UTU) Meulaboh has installed power with a load consisting of the installation of lighting, air conditioning in the room rector and academic faculty, computers and electrical machinery in several laboratories. In this study, carried out the process of energy audits to calculate the level of electrical energy use of a building or the main building on the campus of the University of Teuku Umar (UTU) Meulaboh, then the results were compared with existing standards for consideration to look for solutions saving energy use if the level of energy use exceeds existing standards. Implementation of research conducted at the University main campus Teuku Umar (UTU) Meulaboh based on pamasangan ampere meter used by each building. The study was conducted by taking the object amount of electrical energy consumption on campus and compared with a building area of energy use and multiplied by the occupancy rate of the building, resulting in a value Intensity Energy Consumption (IKE) will be compared with the standard IKE appropriate recommendation. Keywords: Energy, Energy Audit, Energy Conservation, Energy Consumption Intensity (IKE)